Leisure time in Japan: how much and for whom? - Scott M. Fuess (Institute for the Study of Labor (IZA), 2006)
Japan is famous for long working hours. For decades the Japanese government has tried to influence how people spend their free time. In 5-yearly surveys since 1986, the government has surveyed quality of life by gauging how much time people spend daily in various non-economic activities. Using results from the 1986, 1991, 1996, and 2001 surveys, this study determines whether time spent daily on leisure activities has actually changed. Controlling for labor market forces, in recent years Japanese adults have not experienced more leisure time overall. They have increased time spent, one hour per week, in media-oriented leisure; this increase, however, comes at the expense of more outgoing amusements like hobbies, playing sports, or socializing with friends. There is a significant gender gap for leisure time. Shorter work schedules do encourage a more active leisure lifestyle. Leisure is directly related to regular income, but is stifled by bonus pay.
Keywords: 330; time allocation; leisure time and working hours; country studies; Japan